Lipids in 21st Century: Treating Hyperlipidemia to Cut Cardiovascular Mortality - Buckley, Rita (MD Conference Express, 2012)
Every year, 17.1 million lives are claimed by the global burden of heart disease and stroke, 82% of which are in the developing world [World Heart Federation. State of the Heart. Cardiovascular Disease Report 2012]. In the United States, cardiovascular disease is the leading cause of death, responsible for 17% of national health expenditures.